Preparation method of high-surface-capacity sodium-ion battery positive electrode constructed by ionic crosslinking binder
Through the method of mixing ion crosslinking binder from sodium alginate and ferric chloride, the structural instability caused by volume expansion of the positive electrode material of traditional lithium-ion batteries is solved, and the positive electrode of sodium ion battery with high surface load and high surface capacity is achieved, which improves the stability and cycle life of the electrode, and has environmentally friendly characteristics.
Patent Information
- Application Number
- CN202510397030.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure CN119920907A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a method for preparing a positive electrode of a sodium ion battery with high surface capacity constructed by an ion cross-linking binder. Background Art
[0002] With the development of renewable green energy such as photovoltaics and wind power, the demand for energy storage and conversion systems is increasing. Secondary batteries, as an important component of energy storage systems, have attracted much attention. However, traditional lithium-ion batteries are difficult to meet the growing market demand due to limited lithium resource reserves. Therefore, the development and use of batteries using alkali metal elements (such as sodium) with abundant reserves and appropriate costs has become a development trend. The reserves of sodium in the earth's crust are much higher than those of lithium, and its physical and chemical properties are similar to those of lithium, so it is regarded as an effective substitute for lithium.
[0003] Among battery electrode materials, selenium (Se) is considered to be a highly promising cathode material due to its high theoretical specific capacity (675 mAh g⁻¹ / 3253 mAh cm⁻³). However, selenium has a large volume expansion during the electrochemical reaction (expansion rate is about 336%), which can easily cause the electrode structure to collapse, rupture or fall off, seriously affecting the stability and safety of the electrode. Traditional electrodes usually use polyvinylidene fluoride (PVDF) as a binder, but its adhesion is poor and it is difficult to withstand the volume change of the electrode material during the charge and discharge process, making it difficult to prepare a stable high-load electrode.
[0004] In addition, the traditional electrode preparation method relies on highly toxic N-methyl-2-pyrrolidone (NMP) as a dispersant, which has problems such as environmental pollution and complex process. Therefore, it is of great significance to develop a new binder and electrode preparation method that can effectively solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a high surface capacity sodium ion battery positive electrode constructed with an ion cross-linking binder.
[0006] To achieve the above object, the present invention is implemented according to the following technical solutions: The method for preparing a high surface capacity sodium ion battery positive electrode constructed with an ion crosslinking binder of the present invention comprises the following steps: S1: prepare an aqueous solution of sodium alginate and ferric chloride; S2: Mixing aqueous solutions of sodium alginate and ferric chloride, stirring at 15-20 °C for 10 h to obtain an ion-crosslinking binder; S3: mixing the electrode active material, the conductive additive and the ion cross-linking binder in a mass ratio of 8:1:1 to form a slurry; S4: coating the slurry on a current collector to prepare a positive electrode for a sodium ion battery.
[0007] Furthermore, the electrode active material is a selenium composite material, and the preparation method of the selenium composite material is as follows: placing biomass waste in a potassium hydroxide aqueous solution for heat preservation treatment, drying and carbonizing in nitrogen, cooling and washing to neutrality to obtain biomass porous carbon; mixing selenium powder and the biomass porous carbon, heating in argon, to obtain a selenium composite material. The biomass waste is straw, and the mass proportion of selenium in the selenium composite material is 60%. The conductive additive is super P carbon. The current collector is aluminum foil.
[0008] The beneficial effects of the present invention are: The present invention is a method for preparing a high-area capacity sodium ion battery positive electrode constructed with an ion cross-linking binder. Compared with the prior art, the present invention utilizes the ion cross-linking effect between sodium alginate (SA) and ferric chloride (FeCl3) to construct a sodium ion battery positive electrode with a high selenium load. The technical effects are mainly reflected in the following aspects: Simple synthesis method: An ion-crosslinked adhesive with high adhesion and high mechanical stability can be obtained by simply mixing sodium alginate and ferric chloride in an aqueous solution and stirring. No complex processes such as high temperature treatment or UV polymerization are required, which greatly simplifies the synthesis of the adhesive.
[0009] Improving electrode performance: Ion-crosslinking binders can significantly improve the hardness and Young's modulus of the electrode, effectively alleviating the negative impact of selenium's volume expansion on the electrode structure during charging and discharging, thereby improving the stability and cycle life of the electrode.
[0010] High surface loading and high surface capacity: Electrodes prepared using this binder can achieve higher surface loading of active materials and higher volumetric capacity output. For example, at a high surface loading of 12 mg cm⁻², the positive electrode of a sodium-selenium battery can achieve a high surface capacity of up to 9.6 mAh cm⁻².
[0011] Environmental friendliness and scalability: This method does not require the use of highly toxic solvents. Combined with the traditional scraping-coating electrode preparation process, it has the potential for large-scale production and can be expanded to the preparation of electrodes for other energy storage materials.
[0012] No interference with electrochemical activity: The ion-crosslinked binder shows good stability during the charge and discharge process and will not interfere with the electrochemical reaction process of the battery, ensuring the normal operation of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The Fourier transform infrared spectrum of the ion cross-linking adhesive prepared in Example 1; Figure 2The X-ray diffraction patterns and Raman patterns of the selenium element, porous carbon and selenium composite material of Example 1; (a) is the X-ray diffraction pattern, and (b) is the Raman pattern; Figure 3 This is the thermogravimetric curve of the selenium composite material prepared in Example 1; Figure 4 The hardness and Young's modulus of the electrode coated with a common binder and an ion cross-linking binder in Example 1; (a) is a hardness bar graph, and (b) is a Young's modulus bar graph; Figure 5 The cross-sectional scanning electron microscope images of the electrodes coated with the common binder and the ion-crosslinking binder in Example 1 under dry conditions and after being immersed in the electrolyte for 6 hours; (a) is a microscope image of the common binder, and (b) is a microscope image of the ion-crosslinking binder; Figure 6 is the cyclic voltammetry spectrum of the ion-crosslinked binder in Example 1; Figure 7 2 mg cm coated with common binder and ion crosslinking binder in Example 1 -2 The charge and discharge curves of sodium-selenium batteries assembled with surface-loaded selenium positive electrodes at different current densities; (a) is the charge and discharge curve of ordinary binders, and (b) is the charge and discharge curve of ion-crosslinked binders; Figure 8 2 mg cm coated with two binders in Example 1 -2 The rate performance diagram of sodium-selenium battery assembled with surface-loaded selenium positive electrode at different current densities; Fig. 9 12 mg cm coated with ion-crosslinking binder in Example 1 -2 The charge and discharge curves of the sodium-selenium battery assembled with surface-loaded selenium positive electrode at a current density of 0.1C; Fig.10 12 mg cm coated with ion-crosslinking binder in Example 1 -2 The curve of the sodium-selenium battery assembled with surface-loaded selenium positive electrode at a current density of 0.1C; Fig.11 1 mg cm coated with two binders in Example 2 -2 Cycling performance diagram of lithium-selenium battery assembled with surface-loaded selenium positive electrode at 0.1C current density; Fig.12 12 mg cm coated with ion-crosslinking binder in Example 2 -2 Curve diagram of lithium-selenium battery assembled with surface-loaded selenium positive electrode at 0.1C current density. DETAILED DESCRIPTION
[0014] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0015] The method for preparing a high surface capacity sodium ion battery positive electrode constructed with an ion crosslinking binder of the present invention comprises the following steps: S1: prepare an aqueous solution of sodium alginate and ferric chloride; S2: Mixing aqueous solutions of sodium alginate and ferric chloride, stirring at 15-20 °C for 10 h to obtain an ion-crosslinking binder; S3: mixing the electrode active material, the conductive additive and the ion cross-linking binder in a mass ratio of 8:1:1 to form a slurry; S4: coating the slurry on a current collector to prepare a positive electrode for a sodium ion battery.
[0016] The cross-linking process is as follows: the oxygen-containing functional groups on the surface of sodium alginate (SA), namely hydroxyl (-OH) and carboxyl (-COOH), react with the iron ions (Fe 3+ ) produce cross-linking through ionic bonds.
[0017] Furthermore, the electrode active material is a selenium composite material, and the preparation method of the selenium composite material is as follows: placing biomass waste in a potassium hydroxide aqueous solution for heat preservation treatment, drying and carbonizing in nitrogen, cooling and washing to neutrality to obtain biomass porous carbon; mixing selenium powder and the biomass porous carbon, heating in argon, to obtain a selenium composite material. The biomass waste is straw, and the mass proportion of selenium in the selenium composite material is 60%. The conductive additive is super P carbon. The current collector is aluminum foil.
[0018] The high surface capacity sodium ion battery positive electrode constructed with the ion cross-linking binder of the present invention is prepared by the above-mentioned preparation method.
[0019] The ion cross-linking binder of the invention is prepared by mixing and stirring sodium alginate and ferric chloride in an aqueous solution. The ion cross-linking binder is used for preparing a positive electrode of a sodium ion battery.
[0020] The sodium ion battery of the present invention comprises a high surface capacity sodium ion battery positive electrode constructed by an ion cross-linking binder. Example 1
[0021] SA and FeCl3 were stirred in deionized water at a mass ratio of 10000:7 at a temperature range of 15~20 ℃ for 10 h to obtain Fe@SA ion cross-linked binder.
[0022] The preparation of the selenium composite material used is as follows: 3 g of biomass waste (straw) was placed in 50 mL of 2 M potassium hydroxide aqueous solution and kept at 160 °C in a closed autoclave for 6 h. After drying, it was carbonized at 700 °C in nitrogen for 2 h. After cooling, it was fully washed with hydrochloric acid and water until the pH became neutral, and the black powder biomass porous carbon BPC sample was collected by vacuum drying. Selenium powder and BPC were fully mixed in a weight ratio of 6:4 and heated at 260 °C in argon for 20 h. A black particle selenium composite material BPC / Se was produced as the positive electrode active material (selenium accounts for 60% by mass in the sulfur composite material).
[0023] Preparation of selenium positive electrode sheet with ion-crosslinking binder: Specifically, 120 mg of selenium composite material as positive electrode material, 15 mg of super P carbon as conductive additive, and 15 mg of Fe@SA as binder were mixed evenly in water as slurry, coated on aluminum foil into a 6 cm × 6 cm rectangle, and after drying, pressed into a circular electrode sheet with a diameter of 1 cm using a circular tablet press.
[0024] Preparation of ordinary selenium positive electrode sheets: Specifically, 120 mg of selenium composite material as positive electrode material, 15 mg of super P carbon as conductive additive, and 15 mg of SA as binder are mixed evenly in water as slurry, coated on aluminum foil into a 6 cm × 6 cm rectangle, and after drying, pressed into a circular electrode sheet with a diameter of 1 cm using a circular tablet press.
[0025] When assembling the sodium-selenium battery, the above-mentioned electrode sheet was used as the positive electrode, the sodium foil as the negative electrode, and Whatman glass fiber as the separator. When assembling the battery, 10 drops of 1 M sodium perchlorate (NaClO4) electrolyte dissolved in ethylene carbonate (EC) and propylene carbonate (PC) (the volume ratio of the two was 1:1) were added, and the sodium-selenium battery electrochemical test was carried out in the voltage range of 0.5~3 V.
[0026] Figure 1 This is the Fourier transform infrared (FTIR) spectrum of the ion cross-linked adhesive prepared in Example 1. Figure 1 There are two curves in the figure. Curve No. 1 is the FTIR spectrum of SA before cross-linking, and curve No. 2 is the FTIR spectrum of Fe@SA after cross-linking. -1 The peak corresponding to the hydroxyl group shifts to 3423 cm after the addition of metal ions. -1 . Located between 1618 and 1419 cm -1 The peaks corresponding to carboxyl groups shifted to 1614 and 1415 cm-1 after ionic crosslinking. -1From the FTIR spectrum, it can be concluded that the peak shift of the functional groups on the surface of the material before and after cross-linking confirms the occurrence of ionic cross-linking.
[0027] Figure 2 (a) X-ray diffraction spectrum and (b) Raman spectrum of the selenium element, porous carbon and selenium composite material of Example 1. Figure 2 There are three curves in it. Curve NO.1 is the (a) X-ray diffraction spectrum and (b) Raman spectrum of selenium alone, curve NO.2 is the (a) X-ray diffraction spectrum and (b) Raman spectrum of porous carbon, and curve NO.3 is the (a) X-ray diffraction spectrum and (b) Raman spectrum of selenium composite material. After being compounded with elemental selenium material, the porous carbon material still retains the spectral characteristics of porous carbon, and there is no impurity peak of elemental selenium after compounding, which confirms that there is no crystalline selenium or other impurities in the selenium composite material. Therefore, it can be concluded from the X-ray diffraction spectrum and Raman spectrum that the prepared porous carbon can effectively load selenium. Selenium exists in an amorphous form inside the selenium composite material, without any characteristic peaks of crystalline selenium, and the immersion of selenium will not affect the structural characteristics of carbon.
[0028] Figure 3 This is a thermogravimetric (TG) curve of the selenium composite material prepared in Example 1. The results show that the mass proportion of selenium in the selenium composite material is 59.6%.
[0029] Figure 4 (a) Hardness and (b) Young's modulus of electrodes coated with common binder (SA) and ion cross-linking binder (Fe@SA) in Example 1. The results show that the hardness and Young's modulus of Fe@SA coated electrodes are much greater than those of SA coated electrodes, proving that Fe@SA binder has better mechanical properties.
[0030] Figure 5 The cross-sectional scanning electron microscope (SEM) images of the electrodes coated with (a) common binder SA and (b) ion cross-linking binder Fe@SA in dry conditions (dry) and after immersion in electrolyte for 6 h (wet) in Example 1. The results show that the volume expansion of the selenium electrode coated with SA is obvious, while the volume expansion of the electrode coated with Fe@SA is very small, which proves that the Fe@SA binder can effectively maintain the stable structure of the electrode in the electrolyte.
[0031] Figure 6 1 is the cyclic voltammetry (CV) spectrum of the Fe@SA binder in Example 1. The results show that the Fe@SA binder has no electrochemical activity and can exist stably during the charge and discharge process.
[0032] Figure 7 2 mg cm coated with (a) SA binder and (b) Fe@SA binder in Example 1 -2The surface-loaded selenium positive electrode assembled sodium-selenium battery at different current densities (1C = 675 mA g -1 ) under the charge and discharge curve. Figure 7 There are three curves in the graph. Curve NO.1 is the charge and discharge curve at a current density of 0.2C, curve NO.2 is the charge and discharge curve at a current density of 0.5C, and curve NO.3 is the charge and discharge curve at a current density of 1C. The charge and discharge curves of the Fe@SA electrode at various current densities are the same as those of the SA electrode. The results show that doping metallic iron ions into the binder will not affect the electrochemical reaction process of the sodium-selenium battery during the cycle.
[0033] Figure 8 2 mg cm coated with two binders in Example 1 -2 Rate performance diagram of sodium-selenium battery assembled with surface-loaded selenium positive electrode at different current densities. Figure 8 There are two curves in the graph. Curve NO.1 is the selenium positive electrode prepared with SA binder, and curve NO.2 is the selenium positive electrode prepared with Fe@SA binder. The results show that the capacity of the electrode prepared with ion cross-linking binder is better under the same surface load, and this advantage is reflected at different current densities.
[0034] Fig. 9 12 mg cm coated with Fe@SA binder in Example 1 -2 The charge and discharge curves of a sodium-selenium battery assembled with a surface-loaded selenium positive electrode at a current density of 0.1C. The smooth curve represents the stable electrochemical reaction process during the charge and discharge process. The discharge curve has a capacity of 9.6 mAh cm at a cut-off voltage of 0.5 V. -2 It can be concluded that the cathode energy of sodium-selenium battery coated with ion-crosslinking binder can reach 12 mg cm -2 The high sulfur loading on the surface of the nanostructured carbon nanotubes enables a stable electrochemical reaction process and obtains a high capacity of 9.6 mAh cm -2 High surface capacity.
[0035] Fig.10 12 mg cm coated with ion crosslinking binder Fe@SA binder in Example 1 -2 The results show that the sodium-selenium battery can achieve a current density of up to 5.6 mAh cm -2 High reversible surface capacity and can stably cycle 90 times. Example 2
[0036] The difference between Example 2 and Example 1 is that the assembled battery is different. The method for preparing the positive electrode sheet is the same.
[0037] When assembling a lithium-selenium battery, the above electrode sheet was used as the positive electrode, the lithium foil was used as the negative electrode, Celgard 2320 was used as the separator, and 6 drops of 1 M lithium hexafluorophosphate (LiPF6) electrolyte dissolved in ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of the two was 1:1) were added when assembling the battery, and the lithium-selenium battery electrochemical test was performed in the voltage range of 1 to 3 V. Other experimental methods are similar to those in Example 1.
[0038] Fig.11 1 mg cm coated with two binders in Example 2 -2 Cycling performance diagram of lithium-selenium battery assembled with surface-loaded selenium positive electrode at 0.1C current density. Fig.11 There are two curves in the graph. Curve NO.1 is the selenium positive electrode prepared by SA binder, and curve NO.2 is the selenium positive electrode prepared by Fe@SA binder. The results show that the electrode prepared by ion cross-linking binder has better cycle stability under the same surface load.
[0039] Fig.12 12 mg cm coated with ion crosslinking binder Fe@SA binder in Example 2 -2 The results show that the lithium-selenium battery can achieve a current density of up to 4.9 mAh cm -2 The stable reversible surface capacity can be stably cycled for 100 times.
[0040] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a high surface capacity sodium ion battery positive electrode constructed with an ion cross-linking binder, characterized in that: The following steps are involved: S1: prepare an aqueous solution of sodium alginate and ferric chloride; S2: Mixing aqueous solutions of sodium alginate and ferric chloride, stirring at 15-20°C for 10 h to obtain an ion cross-linking binder; S3: mixing the electrode active material, the conductive additive and the ion cross-linking binder in a mass ratio of 8:1:1 to form a slurry; S4: coating the slurry on a current collector to prepare a positive electrode for a sodium ion battery.
2. The method for preparing a high surface capacity sodium ion battery positive electrode constructed with an ion cross-linking binder according to claim 1, characterized in that: The electrode active material is a selenium composite material, and the preparation method of the selenium composite material is as follows: placing biomass waste in a potassium hydroxide aqueous solution for heat preservation treatment, carbonizing it in nitrogen after drying, and washing it to neutrality after cooling to obtain biomass porous carbon; mixing selenium powder and the biomass porous carbon, and heating them in argon to obtain the selenium composite material.
3. The method for preparing a high surface capacity sodium ion battery positive electrode constructed with an ion cross-linking binder according to claim 2, characterized in that: The biomass waste is straw, and the mass proportion of selenium in the selenium composite material is 60%.
4. The method for preparing a high surface capacity sodium ion battery positive electrode constructed with an ion cross-linking binder according to claim 1, characterized in that: The conductive additive is super P carbon.
5. The method for preparing a high surface capacity sodium ion battery positive electrode constructed with an ion cross-linking binder according to claim 1, characterized in that: The current collector is aluminum foil.
6. A high surface capacity sodium ion battery positive electrode constructed with an ion cross-linking binder, characterized in that: The method is prepared according to any one of claims 1 to 5.
7. An ion cross-linking adhesive, characterized in that: The ionic cross-linking binder is prepared by mixing and stirring sodium alginate and ferric chloride in an aqueous solution. The ionic cross-linking binder is used for preparing the positive electrode of a sodium ion battery.
8. A sodium ion battery, characterized in that: A high surface capacity sodium ion battery positive electrode constructed with the ion cross-linking binder according to claim 6.
Citation Information
Patent Citations
Conductive additive-free electrode constructed by conductive crosslinking binder, preparation method and application of conductive additive-free electrode
CN117219774A
Carbon / iron sulfide composite negative electrode material and preparation method thereof
CN118908291A